A construção do conhecimento histórico através das fontes: aproximações e distanciamentos entre as políticas públicas educacionais e as práticas escolares no ensino da História - Nogueira, Laisa dos Santos (2012)
Born from the constant questionings that arise from school practices regarding the teaching of History, the present research revolves around the study of the instructions that are given to the teachers by the Ministry of Culture and Education of Brazil (MEC in Portuguese). Therefore, a reflection is sought, when it comes to the possibilities and limitations of putting into practice in public schools an educational proposal that favors the student as a producer of knowledge by means of critiquing historical documents. For that, a dialogue is thought of to be established about the latest changes in school practices and public policies (notably through the use of the Curricular National Parameters P.C.N. in Portuguese), in addition to an attentive look towards evolution, also in the historical research. By means of this study, it is considered that the indication made *through the use of the Curricular National Parameters lead to a teaching proposal which privileges the analysis and criticism of traces from the past (in its most variable discursive manifestations) as well as bringing closer together the institution and the historical research itself. Meanwhile, the practices of the public school History teachers are taken into account, by means of questionnaires that are given, with the purpose of evidencing that which, in fact is being done inside the middle school classrooms in the city of Rio Grande. From the analysis of the results that these questionnaires provide, it s possible to note that, despite the fact the Parameters (P.C.N.) proposal has not been mentioned by the teachers-collaborators, historical sources are continually utilized as didactic and methodological resources in the classes rendered by the great majority of them. At last, the data gathering is done through a trial proposal in a ninth-grade class in Mate Amargo Municipal School (Rio Grande/RS). Such proposal is organized based on MEC s parameterization given to the elementary 4th cycle school teachers. The student s concept about sources and historical knowledge, as well as the school practices referent to the proposal, lead to an analysis in the concluding part of this research.